Clinical course and prognostic factors of COVID-19 infection in an elderly hospitalized population. (November 2020) - Mostaza, Jose M.; García-Iglesias, Francisca; González-Alegre, Teresa; Blanco, Francisco; Varas, Marta; Hernández-Blanco, Clara; Hontañón, Victor; Jaras-Hernández, María J.; Martínez-Prieto, Mónica; Menéndez-Saldaña, Araceli; Cachán, María L.; Estirado, Eva; et al.
Highlights: Older patients with COVID infection have a similar clinical course than younger subjects. Males have a greater COVID mortality than females. Worsening dyspnea and decline renal function during admission associate with death. Treatment with RAAS inhibitors associates with a greater survival. Abstract: Introduction: Older subjects have a higher risk of COVID-19 infection and a greater mortality. However, there is a lack of studies evaluating the characteristics of this infection at advanced age. Patients and methods: We studied 404 patients ≥ 75 years (mean age 85.2 ± 5.3 years, 55 % males), with PCR-confirmed COVID-19 infection, attended in two hospitals in Madrid (Spain). Patients were followed-up until they were discharged from the hospital or until death. Results: Symptoms started 2–7 days before admission, and consisted of fever (64 %), cough (59 %), and dyspnea (57 %). A total of 145 patients (35.9 %) died a median of 9 days after hospitalization. In logistic regression analysis, predictive factors of death were age (OR 1.086; 1.015–1.161 per year, p = 0.016), heart rate (1.040; 1.018–1.061 per beat, p < 0.0001), a decline in renal function during hospitalization (OR 7.270; 2.586–20.441, p < 0.0001) and worsening dyspnea during hospitalization (OR 73.616; 30.642–176.857, p < 0.0001). Factors predicting survival were a female sex (OR 0.271; 0.128–0.575, p = 0.001), previous treatment with RAAS inhibitors (OR 0.459; 0.222–0.949, p = 0.036), a higher oxygen saturation at admission (OR 0.901; 0.842–0.963 per percentage point increase, p = 0.002), and a greater platelet count (OR 0.995; 0.991–0.999 per 10 6 /L, p = 0.025). Conclusion: Elderly patients with COVID-19 infection have a similar clinical course to younger individuals. Previous treatment with RAAS inhibitors, and demographic, clinical and laboratory data influence prognosis.